Moral Rebellion and Religiusity in Pious Muslim Novels: Chavchay Saifullah and Muhidin M Dahlan Review of Sociology of Literature - Herdi Sahrasad; Muhammad Ridwan (BIRCU, 2019)
This article argues that novelists Muhidin M Dahlan and Chapchay Syaifullah tried to make moral and religious rebellions in their work as a result of existing social conditions. They rebel against normative and established values, old order and social arrangements. They are creative in the context of literature as a fictional world built with the spirit of renewal and enlightenment. And here, imagination is a significant creative process for deconstruction and enlightenment as well as upheaval in religiosity, religious rebelion, religious dissent.In this context, Muhidin and Syaifullah novels do not place religious life as a problem solver. Borrowing Goenawan Mohamad's definition that works that can be categorized as